Effectiveness of Interdisciplinary Based Islamic Religious Education Teaching Materials at State Vocational School 1 Singosari Malang - Ali Matsubir; Syamsurizal Yazid; Abdul Haris; Tuyizere Alice Peace (Tinta Emas Publisher, 2025)
This study aims to develop PAI teaching materials that are valid, interesting, and effective in PAI learning at State Vocational School (SMKN) 1 Singosari. This type of research is development research by adapting the procedural steps of the IQF curriculum development model. Data were collected through tests and questionnaires. The data analysis used in this research is simple linear regression. The results of the expert trial obtained the results of the level of feasibility or validity and the attractiveness of PAI teaching materials with an interdisciplinary approach with good qualifications. Meanwhile, the level of effectiveness measured through pre-test and post-test in the initial field trial of FKIP Unej students showed an increase in learning outcomes reaching 27.89% with the results of calculating the t-test obtained that the t-count value was 13,101 greater than the t-table, which was 2.003. In the follow-up field trial of class X students, it showed an increase in learning outcomes reaching 32.41% with the results of calculating the t-test obtained that the t-count value was 21.005 greater than the t-table, namely 1.990. Thus, it means that PAI teaching materials with an interdisciplinary approach that have been developed are proven to be valid, interesting and effective in improving student learning outcomes at SMKN 1 Singosari.